Meningkatkan Aktivitas, Keterampilan Berpikir Kritis, Dan Hasil Belajar Muatan Ipa Menggunakan Model Lembung Di Sekolah Dasar - Nada Azizah; Raihanah Sari (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
The problem behind this research is because student activity in class is low, and learning outcomes in science content do not reach the KKM that has been determined. This research was conducted with the aim of describing how to increase teacher activity, students' critical thinking skills and learning outcomes. PTK which was held 4 times in class V SDN Anjir Seberang Pasar II.1 with 12 students. The research instrument uses an observation sheet. Then described with tables and graphs. The results showed that the teacher's activities reached very good criteria, the students' activities were very active, the critical thinking skills reached very critical, the classical learning outcomes reached 92%. Based on these findings, it is shown that the application of the LEMBUNG model is capable of teacher and student activity and has a positive impact on learning outcomes. So the researcher suggests that this learning can be used as a reference in improving learning conditions in the classroom and increasing its quality.